2012
DOI: 10.1016/j.ygeno.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of imprinting regulators at the Meg3 differentially methylated region

Abstract: Genomic imprinting at the Delta-like 1 (Dlk1) - Maternally expressed gene 3 (Meg3) locus is regulated by the Meg3 differentially methylated region (DMR), but the mechanism by which this DMR acts is unknown. The goal of this study was to analyze the Meg3 DMR during imprinting establishment and maintenance for the presence of histone modifications and trans-acting DNA binding proteins using chromatin immunoprecipitation. In embryonic stem (ES) cells, where Meg3 is biallelically expressed, the DMR showed variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…4A and B). As previously reported [27], histone H3K4me3 and H3K9me3 were enriched on the maternal and paternal allele of Meg3 promoter, respectively (Fig. 4C).…”
Section: Resultssupporting
confidence: 88%
“…4A and B). As previously reported [27], histone H3K4me3 and H3K9me3 were enriched on the maternal and paternal allele of Meg3 promoter, respectively (Fig. 4C).…”
Section: Resultssupporting
confidence: 88%
“…To demonstrate whether UHRF1 could regulate MEG3 expression in HCC, we altered the expression of UHRF1.The data showed the expression of UHRF1 was negatively associated with MEG3 expression. However, UHRF1 was never reported to be a regulatory factor of MEG3.Interestingly, we found that hypermethylation of MEG3 promoter, which may be responsible to the down‐regulation of MEG3, has been detected in many malignancies . Besides, UHRF1 was reported acting a crucial role in DNA methylation by recruiting DNMT1 to hemimethylated DNA during DNA replication .…”
Section: Discussionmentioning
confidence: 84%
“…There have been multiple efforts to dissect the functions of the maternallyexpressed lncRNAs in the Meg3-Rian-Mirg locus over the past decade (McMurray & Schmidt, 2012;Steshina et al, 2006;Takahashi et al, 2009;Zhou et al, 2010), but definitive results remain elusive. The difficulty is mainly attributable to two major hurdles; namely that 1) there are many DMRs that control imprinting status in upstream, promoter, and exon regions of Meg3, and 2) Meg3 might function in cis to regulate its imprinting status (Matsubara et al, 2015;Ogata & Kagami, 2016).…”
Section: Combinatorial and Individual Roles Of The Meg3-rian-mirg Lncmentioning
confidence: 99%